Cover Image, Volume 42, Number 1, January 2023. Issue 1 (29th December 2022) - Tokita, Yohei; Sugaya, Kimio; Nishijima, Saori; Tsuchiya, Naoko; Hamaguchi, Marie; Yamamoto, Hideyuki
Abstract : Cover : The cover image is based on the Research Article Choreito, a Kampo medicine attenuates detrusor overactivity and bladder pain symptoms in rat tranilast‐induced interstitial cystitis/bladder pain syndrome‐like model by Yohei Tokita PhD et al., https://doi.org/10.1002/nau.25095 .